(untitled) (Bangladesh Journal of Neuroscience, 2026)
Background: Carotid angioplasty and stenting is an emerging treatment option for carotid stenosis to prevent stroke recurrence in ischemic stroke patients with carotid stenosis. Objective: The purpose of the study was to observe the frequency of new brain lesions in ischemic stroke patients after carotid stenting. Methodology: This was a hospital based prospective longitudinal before – after study conducted in the department of neurology, BSMMU. We evaluated 31 ischemic stroke patients who had significant stenosis in the extracranial portion of internal carotid artery during September 2020 to August 2022. MRI of brain (including DWI sequence) was done to each patient to confirm the diagnosis. Vascular imaging by any of the modalities like Carotid Doppler, MRA, or cerebral DSA (Digital subtraction angiography) was done and the degree of stenosis was measured by the North American Symptomatic Carotid Endarterectomy Trial (NASCET) formulae. Those patients who got more than 50% carotid stenosis underwent carotid artery stenting procedure. Then all the patients were followed up by MRI (including DWI sequence) of Brain within 48 hours to see the occurrence of any new DWI lesion. Four patients were lost during follow up. Results: Total 31 patients were analyzed in the study. Mean age of the respondents were 60.2±8.79 years. Within 48 hours of stenting MRI of Brain showed new DWI lesion in 12.9% patients. After Stenting, 75% patients had single DWI lesion on MRI and 25% had multiple lesions. Most of the patients had MCA territory stroke (100%) where capsuloganglionic region was the most frequent location of infarction (100%). Among all the patients who underwent carotid stenting, only 3.2% patients had developed symptomatic new DWI lesion. Conclusion: Carotid stenting with or without angioplasty is a relatively safe procedure with few new DWI lesions on follow-up MRI.